The Mediating Role of Adversity Quotient in The Relationship Between Parental Support and Career Adaptability among Generation Z Vocational High School Students - Hadi, Nia Priscilla Natasya; Salim, Rose Mini Agoes (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to analyze the mediating role of adversity quotient in the relationship between parental support and career adaptability among Generation Z vocational high school students. This quantitative, non-experimental study involved 627 twelfth-grade students from five schools in Jakarta and Banten, aged 16-18 (M=17.2), with a majority of female students (65.6%). Data was collected using the Career Adaptability Scale-5 (CAS-5), Career Related-Parent Support Scale (CRPSS), and Adversity Response Profile-Quick Take (ARP). Data was analyzed using R studio. The results showed that the adversity quotient partially mediated the relationship between parental support and career adaptability. The adversity quotient possessed by Generation Z vocational high school students can help them overcome difficulties in achieving career goals and adapting to the ever-changing career context due to the development of Industry 4.0 and the use of technology in the workplace. Parental support perceived by Generation Z vocational high school students significantly contributes to increasing students' career adaptability. This implies that the role of parents is crucial because the higher the parental support, the more students will have the ability to adapt to changing career contexts, especially Generation Z vocational high school students who will experience career transitions into the workforce.